A secured automated bimodal biometric electronic voting system - Kennedy Okokpujie; John Abubakar; Samuel John; Etinosa Noma-Osaghae; Charles Ndujiuba; Imhade Princess Okokpujie (Institute of Advanced Engineering and Science, 2021)
Insecurity, rigging and violence continue to mar electoral processes in developing nations. It has been difficult to enforce security and transparency in the voting process. This paper proposes a secure and automated bimodal voting system. The system uses three security layers, namely, a unique ID code, a token passcode that expires every five minutes and biometrics (iris and fingerprint). A scanner captures the fingerprint and iris of eligible voters. The fingerprint and iris images stored along with the corresponding particulars in a database. The software implemented is a .net managed code in C#. The result of this system shows the system is transparent, fast and fraud-free. The proposed method had a failure to enroll (FTE) and a failure to capture (FTC) of zero.